Experimental Measurement and Analysis: Collimation and Illumination for Conformity Measuring Instrument Design in X-ray Modality - Fajar, Fathul; Mak’ruf, Muhammad Ridha; Pudji, Andjar; Rizal, Achmad (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
Manual illumination and collimation testing can be affected by subjectivity. Human interpretation and judgment in measuring and adjusting illumination and collimation can vary between individuals, potentially resulting in inconsistent results. The aim of this research is to develop the simplest method for measuring illumination at four points simultaneously and directly storing the measurement data. This objective aims to address the subjectivity issues and improve the reliability and consistency of the testing process, which measures illumination at four points simultaneously and stores the measurement data directly. The method of this study was an experimental measurement and analysis that involved capturing illumination and collimation data using a suitable measuring instrument in an X-ray environment. The collected data is then analyzed to evaluate the suitability of the instrument to the established compliance standards. The module is designed using HC-SR04 sensor as a distance meter and TSL2561 sensor as a light meter. This module is designed using HC-SR04 sensor as a distance meter and TSL2561 sensor as a light meter. In this research, the module has been tested and compared with the results of the comparison tool (Digital Light Meter) and obtained an error value of 1.55% with a module efficiency of 98.45% in the illumination test, and an error of 1.8% with a module efficiency of 98.2% in the collimator test. From this research, it can be concluded that the TSL2561 light sensor can be used to measure the illumination area of the collimator lamp. The contribution of this research is expected to be as follows consistent results from tool testing, provides accuracy of results, is more efficient in cost and energy, and the data will be stored until the next testing time.